To find the value of the function \( y = 18x - 13 \) when \( x = -4 \), we can substitute \(-4\) for \(x\) in the equation.
\[ y = 18(-4) - 13 \]
Calculating \( 18(-4) \):
\[ 18(-4) = -72 \]
Now substitute this back into the equation:
\[ y = -72 - 13 \]
Calculating \(-72 - 13\):
\[ y = -72 - 13 = -85 \]
Therefore, the value of the function when \( x = -4 \) is \( y = -85 \).
None of the provided answer choices (-16, -12.5, -15, -13.5) match this result, indicating that either the equation or the input values might have been miscommunicated. Please verify the values or the equation if needed.